Quality of life of individuals with chronic kidney disease on dialysis - Nadaby Maria Jesus; Gracielly Ferreira de Souza; Clesnan Mendes-Rodrigues; Omar Pereira de Almeida Neto; Deusdélia Dias Magalhães Rodrigues; Cristiane Martins Cunha (Brazilian Journal of Nephrology, 2019)
Abstract Introduction: Chronic kidney disease (CKD) negatively affects the physical and biopsychosocial aspects of the lives of individuals with the disease, thereby affecting the quality of life (QOL) of patients and their families. Objectives: This study aimed to measure the QOL of individuals with CKD and compare the QOL scores of patients with CKD to the scores of disease-free individuals to find factors associated with better QOL. Method: The local Ethics Committee approved this cross-sectional study. The study was carried out at a public clinic and a private hemodialysis clinic. Participants were asked to answer the WHOQOL-BREF and a sociodemographic questionnaire. Statistical tests were used according to the variables of interest and significance was attributed to differences with p-values < 0.05. Results: Nearly two thirds (59%) of the case group members were males and 55% did not have a spouse; 53% were seen at a private clinic and 57% had complications. The variables that more significantly affected QOL were smoking (perception of QOL) (Bi = - 0.4061; p = 0.032), undergoing hemodialysis (general health status) (Bi = - 0.3029; p = 0.034), and duration of sessions (Bi = 0.117; p = 0.039) (environmental domain). Conclusion: The QOL of patients with CKD was significantly lower when compared to controls in the physical and psychological domains. Several variables affected the perception of QOL and should be considered in clinical assessment.